Study on economic power and steam cogeneration potential in the Thai yarn textile industry - Janthana Kunchornrat; Heredia, Juan B.; Surapong Chiraratananon; Dang, Giap Van; Commission of The European Community (Bangkok : Asian Institute of Technology, 1994)
The eco nomic power and steam cogeneration potential in the Thai yarn textile industry are discussed in this study. The study was accomplished through case examples, which had been considerd as representatives of this sectors. For economic and financial evaluation, the operating and costs data of the selected firms were used as basis for analysis. A sensitivity analysis was done by alternative systems like separated generation by diesel generator. The performances all systems were then evaluated for economic and financial viability. As additional information, the implementations and barriers of cogeneration are also presented, together with the government incentives scheme in support of system applications.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Cogeneration of electric power and heat -- Thailand